2010
DOI: 10.1101/gr.106054.110
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive survey of 3′ animal miRNA modification events and a possible role for 3′ adenylation in modulating miRNA targeting effectiveness

Abstract: Animal microRNA sequences are subject to 39 nucleotide addition. Through detailed analysis of deep-sequenced short RNA data sets, we show adenylation and uridylation of miRNA is globally present and conserved across Drosophila and vertebrates. To better understand 39 adenylation function, we deep-sequenced RNA after knockdown of nucleotidyltransferase enzymes. The PAPD4 nucleotidyltransferase adenylates a wide range of miRNA loci, but adenylation does not appear to affect miRNA stability on a genome-wide scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
364
2
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 318 publications
(405 citation statements)
references
References 58 publications
(78 reference statements)
35
364
2
3
Order By: Relevance
“…2A). This finding surprised us, as previously most miRNA 3′ adenylation events appeared to be mediated by PAPD4 and few, if any, by PAPD5 (17). We therefore repeated the PAPD5 knockdown experiment, which again showed a significant decrease in the miR-21+C adenylation ratio (by 71%; P = 2.6e-18; Fig.…”
Section: Significancementioning
confidence: 75%
See 3 more Smart Citations
“…2A). This finding surprised us, as previously most miRNA 3′ adenylation events appeared to be mediated by PAPD4 and few, if any, by PAPD5 (17). We therefore repeated the PAPD5 knockdown experiment, which again showed a significant decrease in the miR-21+C adenylation ratio (by 71%; P = 2.6e-18; Fig.…”
Section: Significancementioning
confidence: 75%
“…Previously, we investigated nontemplated 3′ nucleotide additions to miRNAs by analyzing sequencing data from THP1 cultures in which the nucleotidyl transferases ZFR, PAPD4, PAPD5, PAPD7, and ILF3 were knocked down by RNAi (17). We reanalyzed these data and found that knocking down PAPD5 dramatically decreases the adenylation ratio of miR-21+C (by 74%, P = 2.1e-11; Fig.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…First, the extra nucleotide in the 5′ or 3′ end usually corresponds to the one in the genomic sequence, hence arguing against the addition of a random nucleotide. (We estimated ≈20% of the reads have a nontemplated extranucleotide, mostly A or U, because it is known that some miRs are naturally modified at their 5′ or 3′ end with a uridyl or adenyl residue (41,42). The modification of miRNA ends is a known biological mechanism rather than experimental artifacts.…”
Section: Discussionmentioning
confidence: 99%